Global gene profiling and anti-tumour activity of human mesenchymal stem cells on BV173 B leukaemia cell line - Sarmadi, Vahid Hosseinpour (2016)
In 2013, there were 8.2 million cancer deaths worldwide and cancers were the second leading cause of death after cardiovascular diseases. Thus, it represents one of the major health issues all over the world. Current therapies such as the conventional methods of targeting the tumour cells by non-specific chemotherapy and radiotherapy have not yielded satisfactory outcomes as seen in many cancer remission cases, and an efficient treatment for cancer cells has yet to be identified. The recent development in mesenchymal stem cell research promises an efficient anti-cancer therapy via a possible mode of cell cycle arrest, apoptosis and immunosuppressive activity. Umbilical cord mesenchymal stem cells (UC-MSCs) are considered as post- natal stem cells present in the Wharton’s jelly of the umbilical cord tissue and are considered as an appealing source of adult stem cells for the cell therapy and tissue engineering as they are easily obtained and expanded while maintaining their multi-lineage differentiation potential. The past research studies have shown that UC-MSCs profoundly inhibited the growth of various tumour cells, however, the molecular mechanisms that execute this inhibition have yet to be identified. Although MSCs contribute to the haematopoiesis and support the growth of blood cells but also able to inhibit highly proliferating cells. Therefore, this study aims to investigate the inhibitory effect of UC-MSCs on haematopoietic tumour cells proliferation at in vitro by elucidating the molecular mechanisms and the relevant gene expression profiles.